Peace Education dan Deradikalisasi Agama - Machali, Imam (Jurnal Pendidikan Islam, 2013)
Peace education is a process of acquiring knowledge, development of attitudes, and behaviors to be able to live mutually respectful, tolerant, peaceful, mutual aid and nonviolence. Peace education that is conducted by “FPUB” is to bring into reality the true brotherhood among the believers that are realized by tolerance-active attitude, honesty, respect for religious freedom and faith. The program is implemented in order to deradicalization of religious groups such as discussion and dialogue among religions, social solidarity action, peaceful action, and prayer together.